Babad Awak Salira: Intertekstualitas Naskah Sunda Islami - Isep Bayu Arisandi; Titin Nurhayati Ma'mun; Undang Ahmad Darsa (Perpustakaan Nasional RI, 2021)
This paper shows that the interrelationship between the texts is present in the ancient manuscripts of the archipelago. Babad Awak Salira (BAS) manuscript is a Sundanese manuscript which contains Islamic teachings. The amount of influence contained in Islamic teachings is presented in several stanzas that are bound by rules or meters. The method used in this research is descriptive analysis, with the use of an intertextuality approach in literary works. The analysis using the intertextuality approach shows that the BAS text has links with other texts; Javanese manuscripts and Islamic books. This paper resulted in the findings of several hipogram or text backgrounds that were “borrowed” in the compilation of BAS. At least 11 hipogram were found to be applied, by conversi, expansi, modification, or exerp. This paper shows that an intertextuality approach can be applied to old manuscript objects. Thus, an intertextuality approach will explore and derive borrowed forms from the background text or hipogram. The cultural linkages between Javanese and Sundanese can be recorded in a manuscript. It is seen from the text, that several Javanese macapat metrums are consistently carried over in the BAS manuscript.